Umami taste components in chicken-spices blends and potential effect of aroma on umami taste intensity - Rani Andaleeb; Yiwen Zhu; Ninglong Zhang; Danni Zhang; Muzahir Hussain; Yin Zhang; Yingshuang Lu; Yuan Liu (Food Science and Human Wellness)
In this study, umami taste intensity (UTI) and umami taste components in chicken breast (CB) and chickenspices blends were characterized using sensory and instrumental analysis. Our main objective was to assess the aroma-umami taste interactions in different food matrices and reconcile the aroma-taste perception to assist future product development. The impact of key aroma, including vegetable-note “2-pentylfuran”, meaty “methional”, green “hexanal”, and spicy-note “estragole and caryophyllene” on UTI was evaluated in monosodium glutamate and chicken extract. We found that spices signif icantly decreased UTI and umami taste components in CB. Interestingly, the perceptually similar odorants and tastants exhibited the potential to enhance UTI in food matrices. Methional was able to increase the UTI, whereas spicy and green-note components could reduce the UTI signif icantly. This information would be valuable to food engineers and formulators in aroma selection to control the UTI perceived by consumers, thus, improving the quality and acceptability of the chicken products.